Persepsi Masyarkat terhadap Daerah Perlindungan Laut (DPL) Di Desa Koroe Onowa Kecamatan Wangi-Wangi Kabupaten Wakatobi - Sarifudin, La; Mardin, Mardin; Suriana, Suriana (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2019)
This research was conducted in Koroe Onowa Village, Wangi-Wangi District, Wakatobi Regency. The key informants in this study were capture fishermen, based on fishing gear used such as (fishing rods, nets, arrows, and shellfish collectors), Village Heads and Marine Protected Areas Management Groups who live in Koroe Onowa Village, Wangi-Wangi District, Wakatobi Regency. While the key informant in this study were fishermen on Onowa Koroe Village. The data analysis model in the study is qualitative data analysis carried out interactively and takes place continuously at the research stage so that it is complete. Based on the results of the study it can be concluded that the perception of fishermen does not question the appropriateness of Marine Protected Areas both from the establishment, management, purpose, benefits and rules of Marine Protected Areas, perceived as conservation areas by fishermen in Koroe Onowa Village even fishermen supporting the Marine Protected Area program as a buffer and preservation of the sea and all biota contained in it besides the DPL program opens opportunities for micro and medium enterprises, especially the development of local economies, but management of Marine Protected Areas in Koroe Onowa Village is still not optimal because it allows fishing in the Marine Protected Area as a prohibited area to take it permanently so it is recommended that the implementation of the Marine Protection Area be carried out consistently for marine conservation.